Determinación de la Correlación entre la Actividad Física y la Condición Física con el Rendimiento Académico en Estudiantes de 8° Grado de la Institución Educativa Serrezuela de Madrid, Cundinamarca. - Suarez Cano, Leonardo Fabio (Universidad Antonio Nariño, 2021)
The relationship between physical activity, physical condition and academic performance has been internationally studied. However, reports of this relationship are limited, and its incidence is still controversial. For that reason, this research determined the correlation between these three variables using the PAQ-A questionnaire to determine physical activity, the six Eurofitnes battery test for physical condition, and the academic results for academic performance in mathematics, Spanish, social sciences and natural sciences. The results indicate that men perform better in their physical activity, which is an indicative for a better physical condition. However, this performance does not indicate positive academic results. On the contrary, although women have better academic results, their activity and physical condition are not optimal. In this matter, mathematics and natural sciences shown better relationship with the studied variables. In addition, it is necessary to isolate each of the carried out tests and determine their incidence in relation to the other variables. Finally, these results are promising, since they can be considered as the starting point to continue with the multivariate analysis between physical activity, physical condition and academic performance.